2019
DOI: 10.1002/ar.24087
|View full text |Cite
|
Sign up to set email alerts
|

WARP: A Unique Extracellular Matrix Component of Cartilage, Muscle, and Endothelial Cell Basement Membranes

Abstract: The von Willebrand factor A-domain-related protein (WARP) encoded by the VWA1 gene, is an orphan extracellular matrix protein that is expressed in a subset of ECM structures but whose function is poorly understood. Here, recent advances on understanding VWA1/WARP will be reviewed including analysis of VWA1 reporter and global knock-out mice, interaction studies, and recent transcriptome analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Immunohistochemistry demonstrated SERPINH1/HSP47 to be highly expressed throughout the coronary vasculature and in fibroblasts in human heart, and weak staining was also detected in cardiomyocytes ( Figure 4E-G, Figure S7D). In human cardiac ECs, HSP47 was localized perinuclearly, similarly to what has been demonstrated in other cells types, and consistent with the ER retention motif in its N-terminus ( Figure 4E) [34][35][36] . We also tested, if exercise training can attenuate the expression of SerpinH1, Vwa1 and selected markers of TGF-b signaling/EndMT also in aged mice.…”
Section: Serpinh1 Expression Is Increased By Aging and Obesity And Resupporting
confidence: 86%
“…Immunohistochemistry demonstrated SERPINH1/HSP47 to be highly expressed throughout the coronary vasculature and in fibroblasts in human heart, and weak staining was also detected in cardiomyocytes ( Figure 4E-G, Figure S7D). In human cardiac ECs, HSP47 was localized perinuclearly, similarly to what has been demonstrated in other cells types, and consistent with the ER retention motif in its N-terminus ( Figure 4E) [34][35][36] . We also tested, if exercise training can attenuate the expression of SerpinH1, Vwa1 and selected markers of TGF-b signaling/EndMT also in aged mice.…”
Section: Serpinh1 Expression Is Increased By Aging and Obesity And Resupporting
confidence: 86%
“…VWA1 was primarily known for its expression in cartilage cells, in basement membranes of the peripheral nervous system and in skeletal and cardiac muscle (Fitzgerald et al, 2002;Allen et al, 2008;Fitzgerald, 2019). Subsequent research also revealed a distinct localization of VWA1 in the inner ear vasculature, suggesting a potential role in maintaining its integrity (Duong et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research also revealed a distinct localization of VWA1 in the inner ear vasculature, suggesting a potential role in maintaining its integrity ( Duong et al, 2011 ). Although VWA1 has surfaced in research on several diseases and has been suspected to be associated with neuro-musculoskeletal disorders, to date, no direct disease-causing variants have been directly identified ( Dieppedale et al, 2013 ; Fitzgerald, 2019 ). Zhang et al (2010) previously reported copy number variance of VWA1 and PYGO2 in a patient presenting with mandibulofacial dysostosis and microtia.…”
Section: Discussionmentioning
confidence: 99%
“…The PNPLA2 gene encodes a protein named adipose triglyceride lipase, which is expressed in human tumors and related to tumor aggressiveness 28 . The VWA1 gene encodes von Willebrand factor A-domain-related protein (WARP), the function of which is still unclear 29 . However, there is translational upregulation of VWA1 in hepatocellular carcinoma (HCC), and cell proliferation can be inhibited after knockdown of VWA1 30 .…”
Section: Discussionmentioning
confidence: 99%